2018
DOI: 10.1111/sltb.12514
|View full text |Cite
|
Sign up to set email alerts
|

Last Words: Are There Differences in Psychosocial and Clinical Antecedents Among Suicide Decedents Who Leave E‐Notes, Paper Notes, or No Note?

Abstract: Objective Only a minority of suicide decedents leave a suicide note. Typically, the notes are handwritten on paper; however, electronic suicide notes have been reported with increasing frequency. This emerging phenomenon remains generally under‐researched. The aim of this study was to compare the psychosocial and clinical antecedents of suicide decedents who left E‐notes with those who left paper notes or no notes. Method The study was embedded in the Southwestern Ontario Suicide Study (SOSS). The SOSS was a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Through interviews and other forms of investigations, CMEs/LEOs documented the circumstances surrounding suicide, including whether the decedents left suicide notes and, if so, the content of these notes. Suicide notes included handwritten notes, video messages, and electronic communications, such as text messages and emails (Eynan et al, 2019; Leenaars, 1996). In our study, 30.9% ( n = 1,130) of APIA decedents left suicide notes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Through interviews and other forms of investigations, CMEs/LEOs documented the circumstances surrounding suicide, including whether the decedents left suicide notes and, if so, the content of these notes. Suicide notes included handwritten notes, video messages, and electronic communications, such as text messages and emails (Eynan et al, 2019; Leenaars, 1996). In our study, 30.9% ( n = 1,130) of APIA decedents left suicide notes.…”
Section: Methodsmentioning
confidence: 99%
“…Nonetheless, there is a paucity of research on APIAs’ suicide notes, defined as unsolicited recorded communications about one’s suicide, typically documented by a suicide decedent just before their death (Leenaars, 1996). These notes include handwritten notes, video messages, and electronic communications, such as text messages and emails (Eynan et al, 2019). In the only known published study on APIAs’ suicide notes, Lee and Wong (2020) found that, among adolescent suicide decedents, APIAs were more likely than Black, Latinx, and Native American (but not White) adolescents to have left a suicide note.…”
Section: Theoretical Basis Of the Studymentioning
confidence: 99%
“…378-394). Even suicide letters, traditionally written by hand, are now usually typed ( [64], pp. 1379-1394).…”
Section: Previous Research 21 Suicidal and Presuicidal Discoursementioning
confidence: 99%